2016
DOI: 10.1111/adj.12338
|View full text |Cite
|
Sign up to set email alerts
|

Restorative materials containing antimicrobial agents: is there evidence for their antimicrobial and anticaries effects? A systematic review

Abstract: The aim of this systematic literature review was to investigate whether the incorporation of antimicrobial agents into dental restorative materials truly exerts an antimicrobial effect against common cariogenic bacteria (primary outcome), and whether the inclusion of antimicrobial agents is able to prevent caries around restorations (secondary outcome). MEDLINE, via PubMed, was searched for papers published between 1980 and 30 November 2014. A total of 1126 articles were retrieved. After inclusion/exclusion as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 129 publications
(141 reference statements)
1
7
0
Order By: Relevance
“…Many studies of antimicrobial materials investigate only short-term effects on a low number of species, which may not be indicative of medium- and long-term capability [98]. Many of these studies claim a potential secondary-caries reducing effect, despite not demonstrating this [99]. Ideally studies would be performed in vivo in animal models of caries, however this is not always practical, especially in the development stage of the materials, when optimization requires testing of multiple formulations under standardised conditions.…”
Section: Current Work To Reduce Biodegradation and Secondary Cariesmentioning
confidence: 99%
“…Many studies of antimicrobial materials investigate only short-term effects on a low number of species, which may not be indicative of medium- and long-term capability [98]. Many of these studies claim a potential secondary-caries reducing effect, despite not demonstrating this [99]. Ideally studies would be performed in vivo in animal models of caries, however this is not always practical, especially in the development stage of the materials, when optimization requires testing of multiple formulations under standardised conditions.…”
Section: Current Work To Reduce Biodegradation and Secondary Cariesmentioning
confidence: 99%
“…Alternative strategies to prevent or fight infections are based on adding silver or gold nanoparticles, known for their antibacterial activity, to the cement . In their recent work, Russo et al reported a bone cement containing preformed gold nanoparticles in the 10–20 nm range that improved the antibacterial activity of the cement .…”
Section: Chemical Phenomenamentioning
confidence: 99%
“…Despite the design of a range of antibacterial dental materials and observed antibacterial effects in vitro, recent reviews conclude that there is insufficient clinical evidence to support the effectiveness of antibacterial dental materials against recurrent caries in patients . Furthermore, the problem of microbial resistance against antimicrobial agents is increasing, and this is no different in the case of QAMs .…”
Section: Antibacterial Properties Of Restorationsmentioning
confidence: 99%